Law and Politics in Post Independence Indonesia: A Case Study of Religious and Adat Courts - Lukito, Ratno (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1999)
This paper will address the development of Indonesian law in the post-independence era. In the following pages, this paper will demonstrate that changes in the country's political climate affected born the Islamic and adat (customary) courts,in spire of the inflexibility with which both legal traditions had weathered the political upheavals of the first half of the century. To this end, the place of both adat and religious courts in post-independence Indonesia will be analyzed in light of this political change. Two major avenues of investigation will be discussed. The first explains the debate between